Photo‐Induced Self‐Cleaning and Wettability in TiO2 Nanocolumn Arrays Obtained by Glancing‐Angle Deposition with Sputtering. (19th April 2021) - Fresno, Fernando; González, María U.; Martínez, Lidia; Fernández‐Castro, Marcial; Barawi, Mariam; Villar‐García, Ignacio J.; Soler‐Morala, Jimena; Reñones, Patricia; Luna, Mónica; Huttel, Yves; de la Peña O'Shea, Víctor A.; García‐Martín, José M.
Abstract: In this work, the preparation of regular nanosized columnar structures of titanium dioxide by means of glancing angle deposition with magnetron sputtering (MS‐GLAD) followed by thermal annealing is reported. MS‐GLAD gives rise to metallic titanium columnar structures with regular width and length that after thermal treatment are fully oxidized to form TiO2 nanocolumns that maintain the morphological features of the original metallic ones. Further functionalization with gold by means of multiple ion cluster source results in well‐dispersed Au nanoparticles across the nanocolumns' surface with a narrow size distribution centered at ca. 8.5 nm. The obtained nanostructures show photocatalytic self‐cleaning activity as shown by the elimination of an organic layer deposited on their surface and the detection of hydroxyl radicals. Photoelectrochemical measurements show a better charge separation at the Au/TiO2 interface. In addition, wettability studies show that the degree of hydrophobicity of the surface is increased by the presence of nanocolumns, both in the dark and under UV illumination. This behavior is not modified by the presence of Au nanoparticles on the surface. The obtained results open up interesting implications in the tunability of the properties of nanostructured thin films for this kind of photo‐activated application. Abstract : Glancing angle deposition with magnetron sputtering (MS‐GLAD) has been demonstrated as a powerful technique for the preparation of regular, controlled TiO2 nanocolumnar structures with photoinduced self‐cleaning and hydrophilic properties. Further functionalization with Au nanoparticles by a multiple ion cluster source (MICS) improves photocatalytic activity and maintains the transition of the arrays from hydrophobic to hydrophilic under UV irradiation.